2001
DOI: 10.1159/000046647
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Interstitial Renal Fibrosis Associated with Chinese Herbal Medications

Abstract: Background/Aim: Nephropathy after ingestion of Chinese herbs is known as a rapidly progressive form of interstitial renal fibrosis after a slimming regimen containing aristolochic acid that was identified first in Belgium. Intake of traditional Chinese herbal medicines is very popular in Taiwan. So we looked for similar cases in our hospital. Methods: From 1994 to 1998, we observed 20 Taiwanese patients who underwent renal biopsy for rapidly progressive renal failure of unknown origin. The medical history of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 19 publications
2
53
0
Order By: Relevance
“…30 Intake of Chinese herbs containing aristolochic acid has been reported as the cause of advanced renal failure in Taiwan. [31][32][33] Chinese herbal products containing aristolochic acid, Mu-ton and Fangi have been banned by the Department of Health (DOH) in Taiwan since 2003. The beneficial effect of this action still needs to be observed.…”
Section: Well-established Risk Factors For Ckdmentioning
confidence: 99%
“…30 Intake of Chinese herbs containing aristolochic acid has been reported as the cause of advanced renal failure in Taiwan. [31][32][33] Chinese herbal products containing aristolochic acid, Mu-ton and Fangi have been banned by the Department of Health (DOH) in Taiwan since 2003. The beneficial effect of this action still needs to be observed.…”
Section: Well-established Risk Factors For Ckdmentioning
confidence: 99%
“…The herbs listed here are different from those used in Europe and the United States. 13,14,18,21,[23][24][25][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] This result can be explained by vegetation differences between countries. Studies have shown that herbal mixtures are often considered safe by patients, [19][20][21][22][23] leading to their preferred use.…”
Section: Discussionmentioning
confidence: 99%
“…(National Kidney Foundation, 2006). Reports indicated that herbal therapy was positively associated with chronic kidney disease (Bagnis et al, 2004;Chang et al, 2001;Chang et al, 2007;Guh et al, 2007;Nowack, 2008;Zhou et al, 2007). Safety issue in relation to polypharmacy becomes a challenge to the authority and the medical society.…”
Section: Pharmaco-epidemiological Aspects In Relation To the Risk Of mentioning
confidence: 99%